Reshaping Labour: Organization, Work and Politics -- Edinburgh in the Great War and After - Morris, R. J. (Labour / Le Travail, 1991)
The article reviews the book, "Reshaping Labour: Organization, Work and Politics -- Edinburgh in the Great War and After," by John Holford.
Keywords: BOOKS -- Reviews; HOLFORD, John; Labor economics; Nonfiction; RESHAPING Labour: Organisation, Work & Politics: Edinburgh in the Great War & After (Book)